The effect of dual role conflicts on nurse performance at private general hospitals in Medan and Deli Serdang - Eva Kartika Hasibuan; Lasma Rina Efrina Sinurat (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: Hospital human resources and hospital organizations become one unit. This requires a female nurse to have a high commitment because she must be able to place her position as a woman employed and her responsibilities as a housewife. Career women who uphold the profession will be more likely to experience conflict.Purpose: To determine whether there is an effect of dual role conflict on performing nurses at the Medan City Private General Hospital and Deli Serdang.Method: This study uses a correlational design and cross-sectional. The sampling technique used total sampling. The population was married female nurses and had children who worked at the Medan Advent General Hospital and Sari Mutiara Lubuk Pakam General Hospital, the nurses at Intensive Care Unit, inpatient and outpatient wards of 94 respondents.Results: The finding was 67% has a dual role category and 74.5% nurse performance in a good category, and by chi-square statistical test showed that there was a significant effect between multiple roles on performance as a nurse as a housewife with p-value = 0.045 (p<0.05).Conclusion: Even though dual role conflict is happening in female nurses, that a nurse can still perform well even though she has a high dual role by remaining wise in managing time as effectively as possible so that she can still harmonize employed and housewife, and keep the nursing care services at the hospital provided remain optimal.